CONVERGENCE OF STYLISTIC DEVICES AS A CATEGORY OF REDUNDANCY - Filippova , Olga (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The article considers the linguistic phenomenon of redundancy in a fiction text as an essential factor that ensures an adequate interpretation of information by the addressee. Particular attention is paid to the convergence of stylistic devices, which through multiple stylistic techniques highlights the most significant elements of the text representing the cognitive principle of foregrounding. The functional significance of convergence in a fiction text has been analyzed, and the cognitive function of this linguistic phenomenon has been discussed.